2013
DOI: 10.1007/s00787-013-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Infant’s engagement and emotion as predictors of autism or intellectual disability in West syndrome

Abstract: West syndrome (WS) is a rare epileptic encephalopathy with early onset and a high risk of autistic outcome. The PréAut grid assesses this risk following WS onset by taking into account synchrony and emotion in interactions and by evaluating the baby's active desire to engage in pleasant interactions (especially the infant's early active behaviors that encourage being gazed at or kissed by the mother or to share joy with her). We followed a sample of 25 WS patients prospectively from disease onset and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
1
22
0
8
Order By: Relevance
“…Interestingly, social play is one of the dimensions assessed by the Preaut scale, which also includes items looking at the presence of early active behaviors that encourage being gazed at or kissed by the mother or sharing joy with her. Interestingly, a recent study has shown that infants diagnosed with a West syndrome were 38 times more likely to receive an ASD diagnosis later in life if they had scored high on the Preaut scale at 9 months (Ouss et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, social play is one of the dimensions assessed by the Preaut scale, which also includes items looking at the presence of early active behaviors that encourage being gazed at or kissed by the mother or sharing joy with her. Interestingly, a recent study has shown that infants diagnosed with a West syndrome were 38 times more likely to receive an ASD diagnosis later in life if they had scored high on the Preaut scale at 9 months (Ouss et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In particular children with specific forms of epilepsy, such as infantile spasms or West syndrome (a rare epileptic encephalopathy with early onset, which is often secondary to tuberous sclerosis complex) present higher prevalence of ASD comorbidity (Saemundsen et al, 2008;Berg et al, 2011;Ouss et al, 2014). Although it may be useful Q7 to screen these high risk samples for ASD symptoms, and to refine screening instruments and clinical tools for these specific disorders (Gipson et al, 2014), the insight this research may provide into the etiology and early manifestations of non-syndromic ASD is controversial, as ASD in genetic syndromes (i.e.…”
Section: Research From Other High Risk Samplesmentioning
confidence: 99%
“…E.g. in the case of Tuberous Sclerosis, it has been shown despite common genetic causal involvement that clinical phenotype was bimodal: on one hand a severe phenotype including ID, ASD and epileptic encephalopathies; on another hand, a mild phenotype with normal or borderline intelligence and ASD (Ouss et al, 2014). (2) The targeted impairment must not impact other dimensions, meaning that modularity in cognitive development is always verified.…”
Section: A Trial To Encompass Heterogeneity: Toward a Developmental Amentioning
confidence: 99%